Age related changes and osteochondrosis in swine articular and epiphyseal cartilage: light ane electron microscopy. - Bhatnagar, R (1981)
Age related changes and osteochondrosis in swine were studied using light microscopy and electron microscopy in articular cartilage and light microscopy and epiphyseal cartilage of swine from three days to 30 weeks of age. Thickness, cellularity and vascularity of both the epiphyseal and articular cartilage, decreased as the swine aged. Osteochondrotic changes included formation of "plugs" of cartilage indicating localized failure of ossification and separation and space formation in epiphyseal cartilage. Eosinophilic streaks and space formation in epiphyseal cartilage was observed in relation to epiphyseal separation. Electron microscopy showed a continuous fibrillar layer on the surface of the cartilage corresponding to the lamina splendens of light microscopy. This layer increased in the thickness and showed accumulation of amorphous material between the fibrils with aging. In the matrix, the orientation and distribution of the collagen fibers changed with growth and thicker fibers with clear sub banding were more common in older age groups. Also, necrotic cells, glycogen containing bodies and cellular debris were noticed in the matrix of normal cartilage in old animals. Chondrocytes in the younger cartilage showed accumulation of organelles responsible for protein synthesis; while Golgi bodies, vesicles, lysosomes, well developed foot processes and other inclusions were noticed in older cartilage. Cartilage erosions had a clumped and disrupted lamina splendens on the surface and electron lucent patches in the ground substances of the matrix and chondrocyte cytoplasm.